High-Tocopherol Fraction from Rice Bran (Oryza sativa) Prepared by Low-Temperature Solvent Crystallization Technique - Cahyanine, Miradiah; Estiasih, Teti; Nisa, Fithri Choirun (Fakultas Teknologi Pertanian Universitas Brawijaya, 2008)
Rice bran is by product form rice milling. Rice bran has good nutrition value, such as rich of vitmamin E. Indonesia has a very great amount of rice bran but has not been explored yet. The aim of this research was to know how influence of temperatur and crystallisation duration to tocopherol rich fraction characteristic, and to determine the effective temperature and duration of crystallization in tocopherol purification from rice bran, through solvent crystallization technique in low temperature. This research was conducted by Randomized Block Design with 2 factors. First factor was crystallization temperature (0 and 10°C) and second factors was duration of crystallization (24, 30 and 36 hours). Each treatment was repeated 3 times. The result was analyzed using analysis of variance and continued by LSD and DMRT.Tocopherol content increased from rice bran oil, unsaponifiable matters, and high tocopherol fraction. Temperature of crystallization significantly affected antioxidant activity, free fatty acid content, and peroxide value. Time of crystallization affected tocopherol concentration, antioxidant activity, and peroxide value. The best treatment was obtained from temperature of crystallization of 0°C and crystallization time of 24 hours. The characteristics of this fraction was tocopherol concentration of 17.84%, antioxidant activity of 38.42%, free fatty acid content of 2.28%, peroxide value of 6.45 meq/kg, and color value of 100.Keywords: tocopherol, rice bran, crystalization, solvent, unsaponifiable fraction